CARACTERIZAÇÃO DO DIÂMETRO DE GOTAS DE AEROSSÓIS EM INSETICIDAS DOMISSANITÁRIOS - Silva, A.r. [UNESP]; Leite, M.t.; Ferreira, M.c. [UNESP]; Tambellini, M.v. [UNESP] (Instituto Biológico, 2021)
The objective of this work was to characterize the aspects related to the diameter of household aerosol droplets. The droplet spectra was determined in a particle size analyzer (Mastersizer S®, version 2.19). The experiment was carried out in a completely randomized design, arranged on a 6 x 2 factorial scheme, with six replications. Two samples were evaluated, of 6 different aerosols available on the market and codified as: BAT, REB, RCJ, RAT, SMI and M. The following parameters were analyzed: 1) the percentage of the sprayed volume containing drops with diameter equal to 15 µm or less; 2) the relative amplitude of the diameter of the droplets in the applied spurt; and the 3) the diameter of droplets for which 10% (Dv0.1), 50% (Dv0.5) and 90% (Dv0.9) of the sprayed volumes presented droplets with lesser diameters. The aerosols evaluated presented characteristics of droplets within the limits of effective tolerance according to the official resolution of the national regulating agency.

O objetivo deste trabalho foi caracterizar os aspectos relacionados ao diâmetro de gotas de aerossóis domissanitários. O espectro de gotas foi determinado num analisador de partículas (Mastersizer S®, versão 2.19), utilizando o delineamento inteiramente casualizado em arranjo fatorial 6 x 2, com seis repetições. Avaliaram-se duas amostras, de seis diferentes marcas de aerossóis disponíveis no mercado e codificados como: BAT, REB, RCJ, RAT, SMI e M. Os seguintes parâmetros foram analisados: 1) a porcentagem do volume pulverizado contendo gotas com diâmetro igual ou inferior a 15 µm; 2) a amplitude relativa ao diâmetro de gotas do jato aplicado; e 3) os diâmetros de gotas para os quais 10% (Dv0,1), 50% (Dv0,5) e 90% (Dv0,9) dos volumes pulverizados apresentaram gotas de diâmetro inferiores. Os aerossóis avaliados apresentaram características de gotas que atenderam aos limites de tolerância vigente em resolução oficial da agência reguladora nacional.
CARACTERIZATION OF DROPLET DIAMETER OF HOUSEHOLD INSECTICIDE AEROSOLS
Keywords: Particle analysis; DMV; droplet uniformity; environmental pollutants; aerosol; Análise de partículas; DMV; uniformidade de gotas; poluentes ambientais; aerossol